In-Exchanged CHA Zeolites for Selective Dehydrogenation of Ethane: Characterization and Effect of Zeolite Framework Type - Zen Maeno (Catalysts, 2020)
In this study, the characterization of In-exchanged CHA zeolite (In-CHA (SiO2/Al2O3 = 22.3)) was conducted by in-situ X-ray diffraction (XRD) and ammonia temperature-programmed desorption (NH3-TPD). We also prepared other In-exchanged zeolites with different zeolite structures (In-MFI (SiO2/Al2O3 = 22.3), In-MOR (SiO2/Al2O3 = 20), and In-BEA (SiO2/Al2O3 = 25)) and different SiO2/Al2O3 ratios (In-CHA(Al-rich) (SiO2/Al2O3 = 13.7)). Their catalytic activities in nonoxidative ethane dehydrogenation were compared. Among the tested catalysts, In-CHA(Al-rich) provided the highest conversion. From kinetic experiments and in-situ Fourier transform infrared (FTIR) spectroscopy, [InH2]+ ions are formed regardless of SiO2/Al2O3 ratio, serving as the active sites.